Pengaruh Budaya Kerja Terhadap Kinerja Karyawan Pada PT.Golden Daru Utama Kabupaten Aceh Besar - Rifana Amara Putri; Widyawati Widyawati; Romano Romano (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
Performance is everything that an employee does which can affect his contribution to a company. Employee performance is influenced by many factors, one of which is work culture. Work culture is a habit that is repeatedly carried out by employees in an organization which is formed from the existence of traditions (customs), religions, and norms. PT.Golden Daru Utama has a work culture where the implementation tends not to be maximal such as in terms of discipline, professional attitude, lack of innovation which is feared will degrade employee performance at the company. The purpose of this study was to determine the effect of work culture on employee performance at PT. Golden Daru Utama, Aceh Besar District. Primary data used in this study were obtained from interviews and questionnaires distributed to permanent employees of PT. Golden Daru Utama. The data analysis technique used is rank spearman correlation. The results of this study indicate that the correlation between work culture and employee performance is strong, with a positive correlation coefficient, which means that work culture and employee performance have a unidirectional relationship, meaning that the better the work culture created by the company, the better the employee's performance will be. to increase. And it is also known that work culture has a significant effect on employee performance at PT. Golden Daru Utama, this can be seen from the significance value of 0.026 which is smaller than () 0.05, therefore ho rejected and ha accepted. Based on the coefficient of determination, it is known that work culture affects employee performance by 53.29%, and the remaining 46.71% is influenced by other variables not examined in this study